Pemberian Pupuk Kandang Ayam dan POC Limbah Sayur terhadap Pertumbuhan dan Produksi Tanaman Pakcoy (Brassica rapa L.) - Hazid Zulfinur Lubis; Efi Said Ali; Asmara Sari Nasution (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2026)
Pakcoy is a leafy vegetable that is rich in nutrients and increasingly popular in the market. Decreasing soil fertility is a major problem in pakcoy cultivation, so an environmentally friendly fertilization approach using organic materials is needed. This research examines the effect of chicken manure and liquid organic fertilizer (POC) from vegetable waste, as well as the interaction between the two, on the growth and yield of pakcoy. The research was conducted in Medan Marelan, North Sumatra, from August to October 2025, using a random factorial group design with two factors and three repetitions. First factor: The dose of chicken manure (without fertilizer, 0.5 kg plot-1, 1 kg plot-1). Second factor: POC concentration of vegetable waste (without POC, 2 ml L-1, 4 ml L-1, 6 ml L-1).Observed parameters: Plant height, number of leaves, leaf area, plant wet weight, and root length. Giving chicken manure, vegetable waste POC, or a combination of both does not have a significant effect on all growth parameters and crop yields. Factors that are expected to affect: Environmental conditions and relatively short pakcoy growth period.